Work Flexibility, Work–Life Balance, and Job Outcomes among Generation Z Auditors in Indonesian - Muhammad Habibie; Pigo Nauli (Journal of Accounting Science, 2026)
General Background: The increasing turnover rate among Generation Z auditors in Indonesian accounting firms reflects a growing mismatch between traditional auditing work systems and younger employees’ expectations for flexibility and work–life balance, as the auditing profession is commonly characterized by rigid working hours and intensive workloads that may weaken auditors’ loyalty and job satisfaction. Specific Background: Although work flexibility is increasingly recognized as an important human resource practice, empirical studies in the auditing profession particularly in the Indonesian context, remain limited and have not sufficiently explained its role in shaping auditors’ attitudes and outcomes. Knowledge Gap: There is a lack of empirical evidence explaining the underlying mechanism linking work flexibility to auditor loyalty and job satisfaction, especially regarding the mediating role of work–life balance among Generation Z auditors. Objective: This study aims to examine the effect of work flexibility on auditor loyalty and job satisfaction, with work life balance serving as a mediating variable. Methods: Using a quantitative approach, data were collected from 120 Generation Z auditors working in Indonesian accounting firms and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results: The findings show that work flexibility has a positive effect on work–life balance and auditor loyalty but does not have a direct effect on job satisfaction; instead, work–life balance fully mediates the relationship between work flexibility and job satisfaction. Novelty: This study extends Social Exchange Theory in the auditing context by demonstrating that work flexibility is perceived primarily as a form of organizational support rather than a direct source of job satisfaction. Implication: Practically, the study suggests that implementing flexible work arrangements can enhance auditors’ well-being, strengthen organizational loyalty, and support the retention of Generation Z talent in Indonesian accounting firms.